2015
DOI: 10.1111/jfbc.12181
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Polyphenolic RichMoringa oleifera Lam. Extracts in Food Systems

Abstract: Moringa oleifera Lam. has long been used in traditional medicine and for culinary purposes. This study aimed at determining the phenolic content as well as the antioxidative properties of leaf and pod extracts of M. oleifera Lam. in vitro and in mayonnaise and bulk sunflower oil. The methanolic leaf and pod extracts (MLE and MPE) had the highest phenolic content and exhibited the highest antioxidant activities in the Ferric Reducing Antioxidant Potential (FRAP) assay (1,298 ± 4.1 μmol Fe [II]/g fresh weight) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Metal chelating capacity is desirable to decrease the concentration of transition metals, causing lipid peroxidation. In this assay, EDTA had slightly higher chelating activity as compared to JSE, and similar results were found by Bholah et al [24] in Moringa oleifera Lam. extracts and Pal et al [12] in red rose petal extracts.…”
Section: Metal Chelating Activitysupporting
confidence: 90%
“…Metal chelating capacity is desirable to decrease the concentration of transition metals, causing lipid peroxidation. In this assay, EDTA had slightly higher chelating activity as compared to JSE, and similar results were found by Bholah et al [24] in Moringa oleifera Lam. extracts and Pal et al [12] in red rose petal extracts.…”
Section: Metal Chelating Activitysupporting
confidence: 90%
“…In this sense, Moringa oleifera Lam (Moringaceae) has been documented as a rich plant of bioactive compounds (e.g., polyphenols, carbohydrates, fatty acids and biofunctional peptides) with several advantages for human health and food applications [2]. Earlier studies focused mainly in the polyphenol content since it has been reported that these compounds have antioxidant abilities that may be used for human consumption [3][4][5]. However, they are sensitive to several factors used in food processing operations (pH, water activity, light conditions, oxygen and temperature).…”
Section: Introductionmentioning
confidence: 99%
“…The use of the leaves of MO as a food fortificant is common practice in African countries such as Ghana, Nigeria, and Ethiopia [33]. They are also used as a source of antioxidants when added to other foods, like mayonnaise and bulk sunflower oil [34]. Moreover, moringa leaves have good functional properties for use in ready-to-eat food products or snacks, such as ribbon-shaped toasted products [35].…”
Section: Tac and Tpc Values For Fourth-range Vegetable Packs With Ormentioning
confidence: 99%